Path analysis of energy economic management standardization in the context of carbon neutralization and carbon peak - Liu, Jilu (Frontiers in Ecology and Evolution, 2023)
Carbon neutrality refers to the process of reducing greenhouse gas emissions in some way, thus slowing down global warming. It can be achieved through tree planting and other ecological measures, as well as through industrial technology, such as capturing and storing carbon dioxide to reduce the emission of carbon dioxide in the atmosphere. Carbon peak refers to the process that the concentration of carbon dioxide emitted by human beings reaches the highest point and then begins to decline. These two concepts are both important aspects of climate change governance. They have a great impact on many enterprises in energy, industry, construction, transportation and other fields, thus changing the development pattern of related industries and generating many new investment and development opportunities. This paper put forward the path analysis of energy economic management standardization in the context of carbon neutralization and carbon peak, with the purpose of studying the development prediction of energy economic management under low carbon conditions. The algorithm proposed in this article was an energy consumption analysis algorithm based on IPAT model, which could be combined with IPAT model to analyze and process energy consumption data. In addition, by analyzing and evaluating the contribution of various factors, people could better understand the impact of energy consumption on the environment and formulate corresponding solutions. Through the experimental analysis of energy economic management based on carbon neutrality and carbon peaking, the results showed that in 2013-2017, under the baseline scenario, carbon emissions increased with the year, from 9.25 billion tons to 10.48 billion tons. Under the carbon neutral scenario, its carbon emissions were 9.22 billion tons, 9.24 billion tons, 9.22 billion tons, 9.19 billion tons and 9.21 billion tons respectively. Obviously, under the carbon neutral scenario, carbon emissions could be better controlled through carbon neutral and carbon peak strategy. Through these experimental prediction results, it can be proved that carbon neutralization and carbon peaking play an excellent role in promoting energy economic management. At the same time, this paper also provides valuable reference information for further research on carbon neutralization and carbon peak.